1985
DOI: 10.1143/jjap.24.l143
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for the DX Center Being a Substitutional Donor in AlGaAs Alloy System

Abstract: An experimental result that the DX center appears in GaAs:Si and GaAsd:Sn under hydrostatic pressure of about 30 kbars has been obtained for the first time. This indicates clearly that the DX center in the AlGaAs alloy system is due to a substitutional donor itself (not a complex referred to as “DX”). The change in nature from the the shallow donor to the deep DX center is discussed based on the complex multivalley conduction band structure of GaAs under various pressures and of AlGaAs with various composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
43
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(50 citation statements)
references
References 19 publications
7
43
0
Order By: Relevance
“…The DX center is an important defect in semiconductors that converts a shallow donor into a deep level [14][15][16][17] . Thus it is a major "killer" defect for the saturation of free-electron carrier concentration in the doping process [18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DX center is an important defect in semiconductors that converts a shallow donor into a deep level [14][15][16][17] . Thus it is a major "killer" defect for the saturation of free-electron carrier concentration in the doping process [18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Several structures for the DX center have been proposed in the literature, such as the broken-bond model (BB-DX) and the α and β cation-cation bond model (CCB-DX) [18][19][20]23 . In general, DX centers can be stabilized by pushing up the conduction band either by pressure, alloying, or quantum confinement 16,17,24 . For GaAs and other III-V and II-VI semiconductors, calculations have shown that the cation site donor-induced DX centers are easier to form than the anion site donor-induced ones 23,25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…The DX centers in bulk semiconductors have been intensively studied for many years especially in the 1980s and 1990s [7][8][9]. Nonetheless, an investigation of DX-centers and the effects on low dimensional systems are still ongoing processes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the DX center in GaAs:Si, under hydrostatic pressure, 1 and in AlGaAs:Si [2][3][4] has been the subject of intense investigation in the last 20 years. Perhaps the most dramatic consequence of the defect is persistent photoconductivity where illumination at low temperatures produces a change in conductivity that persists at low temperatures after the illumination is removed.…”
mentioning
confidence: 99%